Comparison of rotational and standard methods of i-gel® insertion in patients of advanced age undergoing general anesthesia: a randomized clinical trial. Issue 12 (December 2022) - Duan, Jinjuan; Sun, Linglu; Lu, Yao; Wang, Shengbin
Objective: This study was performed to compare the performance of rotational versus standard insertion of the i-gel® (Intersurgical, Wokingham, Berkshire, England) in patients of advanced age. Methods: This single-center, randomized, double-blind trial involved 140 patients of advanced age undergoing general anesthesia. The patients were randomized into the standard group and rotational group. The primary objective of this study was to compare the success rate of the first attempt. The secondary outcome indicators were the insertion time and postoperative complications. Results: The placement success rate on the first attempt was significantly higher in the rotational group than in the standard group (92% vs. 73%, respectively). The overall success rate was 100% for the rotational method and 95% for the standard method. The mean ± standard deviation insertion times were similar (15 ± 7.34 vs. 14 ± 7.26 s, respectively). The incidence rates of blood staining of the i-gel®, hoarseness, and sore throat did not increase with the rotational technique and were not significantly different from those of the standard method. Conclusion: Compared with the standard method, the rotational method of i-gel® insertion had a higher success rate and did not increase the insertion time and complications in patients of advanced age. Trial registration: This trial was registered at the Chinese Clinical Trial Registry (ChiCTR2000038763, Date of registration: 30/09/2020).